Misteri jed rahsia - Nazir, Faridah (Wacana MBM, 2020)
The novel revolves around Busu, a man who has a defense. The defense was found accidentally in the forest when Busu cut down the logs. Busu accepted the defense in the hope that he could protect himself and his children. But by God's destiny, Busu has married one of his advocates. No one in the Busu family knew about his secret until the appearance of Hisham, his son-in-law. But Hisham could not prove the presence of the defense because he was the only one who could see it with the naked eye. However, the presence of Izad, Busu's new son-in-law, has been able to unravel Busu's secret that has been kept for many years.